Detection of Antioxidant Phytochemicals Isolated from Camellia japonica Seeds Using HPLC and EPR Imaging - Chalermpong Saenjum; Thanawat Pattananandecha; Kouichi Nakagawa (MDPI AG, 2020)
In this study, we investigated the formation of stable radicals and compounds related to antioxidants in Camellia japonica seeds using high performance liquid chromatography (HPLC) and X-band electron paramagnetic resonance imaging (EPRI). The C. japonica seed coat extracts exhibited antioxidant activity in both in vitro and cell-based studies. The extracts inhibited reactive oxygen and reactive nitrogen species production in cell-based studies. HPLC chromatograms indicated that hydrophilic antioxidant compounds-namely, gallic acid, gallocatechin, epigallocatechin, caffeine, catechin, epicatechin, and epicatechin gallate-were found in the methanolic extract. Lipophilic antioxidant compounds-including α-tocopherol, γ-tocopherol, β-tocopherol, δ-tocopherol, α-tocotrienol, γ-tocotrienol, and δ-tocotrienol-were found in the hexane extract. EPRI primarily detected paramagnetic species in seed coats. These radical species were stable organic radicals based on the peak-to-peak line width and g-values. The signals from these stable radicals were strong and stable with a g-value of 2.002. Noninvasive EPRI of the radicals present in C. japonica seeds indicated that the stable radicals were essentially located in the seed coats. The EPRI of the cotyledon demonstrated that additional radicals were localized at an apex of the cotyledon. The results indicated that the stable radicals detected by EPRI and the hydrophilic and lipophilic antioxidant compounds analyzed by HPLC were related to antioxidant reactants and products.